Reduced complication rates of percutaneous transhepatic biliary drainage with ultrasound guidance. Issue 7 (2nd March 2017) - Wagner, Andrej; Mayr, Christian; Kiesslich, Tobias; Berr, Frieder; Friesenbichler, Paul; Wolkersdörfer, Gernot W.
ABSTRACT: Background: We aimed to analyze the benefits of adding ultrasound (US) guidance to the standard fluoroscopically assisted percutaneous transhepatic biliary drainage (F‐PTBD). We also performed a systematic literature review of success and complication rates of US‐PTBD in a wide field of indications. Methods: We evaluated a total of 81 US‐PTBDs carried out in our institution, 74% of which were part of the management of malignancy. In addition, we compared our results with those of a total of 5, 272 procedures (3, 779 F‐PTBD and 1, 493 US‐PTBD) reported in the literature. Results: US‐PTBD was technically successful in 94% of attempts with a mean of 2.2 needle passes. Procedural success was achieved in 86% of cases. There were no procedure‐related deaths or severe complications. Minor complications were catheter dislodgement (15%) as well as one case each of a porto‐biliary fistula, hematoma, and biloma. A systematic review of the literature also showed that US‐PTBD has a similar technical success rate to F‐PTBD but lower median rates of severe early complications (0% versus 8%) and procedural death (0% versus 1%). Conclusions: Given our results and our review of the literature, US‐PTBD is as effective as F‐PTBD and has significantly lower complication rates. US‐PTBD should be preferred to F‐PTBD. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45 :400–407, 2017